Treatise De adventu Medici ad aegrotum — the attitude of doctors to the disease and its treatment, an example of the Salerno Medical School - Yu. V. Rodionova (Российский журнал истории Церкви)
The article presents a translation of an anonymous treatise De adventu Medici ad aegrotum in Russian, the origin of which is attributed to the Salerno School of Medicine. Using the example of the treatise, it is possible to determine what characteristic the doctors of the XIII century attached to the disease, and the tasks of the doctor’s craft.The philosophy of healing the body is based on an understanding of nature as an instrument created by God, and not on the influence of divine power (will), which makes a decision about healing in each individual case (individually for each patient). The origin of the disease of the body is considered a consequence of some kind of influence on substance, an overabundance of substance affects nature, which resists and strives for the return of balance and its integrity.